2009
DOI: 10.1002/apj.262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaO on NH3 + NO + O2 reaction system in the absence and presence of high concentration CO2

Abstract: The effect of CaO on the NH 3 + NO + O 2 reaction system at 650-850• C was investigated. High CO 2 concentration was added to investigate the effect of CaCO 3 on this reaction system also. Experimental results showed that CaO had a strong catalytic effect on NH 3 decomposition, NH 3 oxidation by O 2 to NO, and NO reduction by NH 3 in the absence of O 2 . The overall effect of CaO on the NO + NH 3 + O 2 reaction was to enhance NH 3 oxidation by O 2 to produce more NO. A small amount of NO 2 and no N 2 O was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Previous studies of NH 3 oxidation over CaO have indicated that -CaN would be formed after NH 3 adsorbed on the CaO surface, and then the formed -CaN would react with O 2 to reproduce CaO and NO, or would react with NO to produce N 2 O (6). Considering almost no N 2 O has been found during the oxidation of NH 3 over CaO in the stream of NH 3 + NO + O 2 + N 2 (6,30), -CaN reacting with NO is of minor importance, suggesting that reaction 4 is of minor importance under this condition. Therefore, the main reaction is -CaN reacting with O 2 to form CaO and NO and providing surface O to reaction 5.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies of NH 3 oxidation over CaO have indicated that -CaN would be formed after NH 3 adsorbed on the CaO surface, and then the formed -CaN would react with O 2 to reproduce CaO and NO, or would react with NO to produce N 2 O (6). Considering almost no N 2 O has been found during the oxidation of NH 3 over CaO in the stream of NH 3 + NO + O 2 + N 2 (6,30), -CaN reacting with NO is of minor importance, suggesting that reaction 4 is of minor importance under this condition. Therefore, the main reaction is -CaN reacting with O 2 to form CaO and NO and providing surface O to reaction 5.…”
Section: Discussionmentioning
confidence: 95%
“…To provide clean and safe drinking water through the urban water supply system, water is usually chlorinated to prevent microbial contamination (Yu & Shi 2010). For example, in China, a free chlorine content of !0.3 mg L À1 after 0.5 h of standing at the end point of an urban water supply system is required (Li et al 2010). However, a high concentration of the chlorine in the drinking water may result in serious health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…CaO also catalyzes reactions between NH 3 and NO in an O 2 -free atmosphere [ 5 , 14 ]. When O 2 is present, these reactions do not apply, and the main effect of CaO is to catalyze NH 3 oxidation with high NO selectivity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%